Penetapan Kadar Flavonoid Total Ekstrak Etanol 96% Daun Gaharu (Aquilaria malaccensis Lam) dengan Spektrofotometer UV-Vis - Indriani, Lusi; Dewi Gulyla Hari; Arabella Natasya; Nurdina Putri (LPPM, Universitas Muhammadiyah Riau, 2024)
Gaharu leaves (Aquilaria malaccensis Lam) are a type of plant commonly used as a raw material for pharmaceuticals, cosmetics, and perfumes due to its secondary metabolic compounds such as flavonoids, alkaloids, terpenoids, steroids, and quinones. This study aims to determine the total flavonoid content of 96% ethanol extract of gaharu leaves using UV-Vis spectrophotometry. Gaharu leaves were extracted using the Microwave-Assisted Extraction (MAE) method with 96% ethanol as the solvent. The resulting extract was then qualitatively tested and the flavonoid content was measured using UV-Vis spectrophotometry with quercetin as the standard. The results of the determination of the total flavonoid content of the 96% ethanol extract of gaharu leaves were 2.539 ± 0.005% equivalent to quercetin.